2023
DOI: 10.3390/su152015125
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Digital Economy on Transformation and Upgrading of Industrial Structure: A Perspective Based on the “Poverty Trap”

Jianing Pang,
Yimeng Zhang,
Fangyi Jiao

Abstract: Breaking the “poverty trap” has gradually become the core topic of economic research. The transformation and upgrading of industrial structure is considered an essential means to break the “poverty trap”. How to use the digital economy effect to change the allocation of capital and labor factors and realize the transformation and upgrading of industrial structure is a significant issue in this paper. The study focuses on examining the development of China’s digital economy between 2013 and 2021, uses the entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Moreover, digital trade includes digital services trade, and its development is likely to promote the growth of other service industries such as e-commerce, leading to the shift from the secondary sector to the tertiary sector. These industries have environmentally friendly characteristics and contribute less to environmental pollution, pressuring energy-intensive and highly polluting industries to undergo digital transformation 21 . Consequently, it fosters the growth of green and low-carbon industries, ultimately leading to a reduction in carbon emissions 22 .…”
Section: The Impact Of Digital Trade On Carbon Emissionsmentioning
confidence: 99%
“…Moreover, digital trade includes digital services trade, and its development is likely to promote the growth of other service industries such as e-commerce, leading to the shift from the secondary sector to the tertiary sector. These industries have environmentally friendly characteristics and contribute less to environmental pollution, pressuring energy-intensive and highly polluting industries to undergo digital transformation 21 . Consequently, it fosters the growth of green and low-carbon industries, ultimately leading to a reduction in carbon emissions 22 .…”
Section: The Impact Of Digital Trade On Carbon Emissionsmentioning
confidence: 99%
“…The evolution of big data has significantly propelled digital development and transformation across various industries, facilitating the acceleration of enterprises' industrial structure upgrading and transformation [72,73]. Research has demonstrated that the digital economy enhances industrial structure upgrading, exerting a more substantial influence on the rationalization of industrial structures than on the advancement of industrial structures [74,75].…”
Section: Hypothesesmentioning
confidence: 99%
“…Industrial structure upgrading implies the process of evolution from primary to advanced level [34]. With the acceleration of the global digitalization process, the digital economy has become an essential engine for promoting regional industrial structure upgrading [35], and resourcebased cities are no exception. Due to the excessive reliance on natural resources, the industrial structure of most resource-based cities is relatively single, which crowds out the space for the development of new industries to a large extent.…”
Section: The Digital Economy and Industrial Structural Upgradingmentioning
confidence: 99%